(untitled) (Student’s Journal of Health Research Africa, 2023)
Introduction: Loss of hearing during early infancy leads to delayed development of language, communication, and cognition which affects the social, emotional, and academic achievements of a child. Early identification of hearing impairment improves age-related language and communication skills. Aim & Objectives: To find out the prevalence and profile of hearing loss among high-risk neonates in a hospital setup. Material and Methods: This was a prospective observational study being conducted over two years at VIMSAR, Bulra, Sambalpur, Odisha. 264 high-risk neonates admitted to Neonatal Intensive Care Unit were screened using evoked otoacoustic emission (EOAE) and Brainstem Evoked Response Audiometry (BERA). Neonates who tested refer on EOAE were subjected to BERA and those having a unilateral or bilateral hearing threshold for more than 40 dB in BERA were defined as hearing impaired. Results: Most of the study neonates were having multiple significant risk factors. Multivariate logistic regression analysis of significant risk factors for hearing loss revealed gestational diabetes of the mother, mechanical ventilation for more than 5 days, hyperbilirubinemia requiring exchange transfusion, hypo-glycemia during the early neonatal period, and duration of hospitalization for more than 5 days were the independent risk factors associated with hearing loss. Conclusion: This study implies a high incidence of hearing impairment in neonatal intensive care unit(NICU) graduates and a change in the distribution of risk factors for hearing loss. Gestational diabetes, mechanical ventilation for more than 5 days, hyperbilirubinemia with exchange transfusion, neonatal hypoglycemia, and NICU stay for more than 5 days were significant independent clinical risk factors for predicting hearing impairment in high-risk neonates. Recommendation: Universal newborn screening for hearing loss in high-risk neonates and early identification of risk factors and exposure reduction should be done, so that the devastating effects of hearing impairment could be prevented before it starts.